Development of the Brazilian Portuguese version of the “Grading scale for idiopathic normal pressure hydrocephalus”: cross-cultural adaptation, reliability and validity - Maria Izabel Romão Lopes; Juliana Benevenuto Tornai; Fernanda Letkaske de Miranda Jeng; Bianca di Virgilio Lopes; Gabriel André da Silva Mendes; Matheus Fernandes de Oliveira; Fernando Campos Gomes Pinto (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective: The current study translated to Portuguese and validated the normal pressure hydrocephalus (NPH) scale originally developed in English as the Grading Scale for Idiopathic Normal Pressure Hydrocephalus. Methods: Following Guillemin's validation protocol, the last version of the Portuguese NPH scale was applied to 121 consecutive patients with a diagnosis of normal pressure hydrocephalus (73 men and 48 women) from the Group of Cerebral Hydrodynamics from July 2010 to March 2012. Results: The mean age was 71.09 years old, ranging from 35 to 92 years. The rate of agreement and reproducibility was high, as confirmed by Cohen's Kappa coefficient, with excellent intraobserver correlation for the NPH scale items individually evaluated: gait (0.80), dementia (0.90) and incontinence (0.87). Conclusions: The Portuguese version of the Grading Scale for Idiopathic Normal Pressure Hydrocephalus was successfully translated and validated for use in Brazilian patients.